ON THE SEPARATION OF SOLAR AND LUNAR CYCLES - Sidorenkov, M. S.; Zhigailo, T. S. (Одеські астрономічні публікації, 2014)
The synodic rotation period of the Sun nearly coincides with the sidereal rotation period of the Moon (27.3 days). The 11-year cycle of solar activity coincides with the eclipse cycle Tritos. The secular cycle of solar activity is close to the 93-year lunar cycle. Due to these coincidences, the cause of monthly, 11-year, and secular periods and their super harmonics in terrestrial processes is attributed to the Sun by solar-terrestrial researchers and to lunisolar tides by geophysicists. The possibilities of separating the solar and lunar cycles by applying spectral analysis, examining frequency differences, and detecting beats and resonances are discussed in this talk.